PHOSPHATE CRYSTALLURIA IN VARIOUS FORMS OF UROLITHIASIS AND POSSIBILITIES OF ITS PROGNOSTICATION IN PATIENTS WITH PHOSPHATE STONES - O. V. Konstantinova; E. K. Yanenko (Исследования и практика в медицине, 2017)
Purpose. Definition of types of crystalluria in various forms of urolithiasis and biochemical signs of phosphate crystals in the urine, while phosphate urolithiasis (infectious origin).Patients and methods. The study involved 144 patients with recurrent urolithiasis — 75 women and 69 men. Of these, 46 — diagnosed calculi with uric acid, 44 — calcium oxalate or mixed with a prevalence of calcium oxalate, in 54 — phosphate rocks (carbonate-apatite and/or struvite). The age of patients ranged from 21 to 74 years. 93 people have been under long-term, within 2–15 years, outpatient observation. The examination included the collection of anamnesis, general and microbiological analysis of urine, biochemical blood serum and urine on 10 indicators, reflecting renal function, state of the protein, water and electrolyte metabolism, uric acid metabolism, the chemical composition of the stone analysis.Results. It was found that in patients with calcium oxalate stones phosphaturia has been diagnosed in 2% of cases. And, along with calcium phosphate crystals they had oxalate crystals. In patients with phosphate urolithiasis phosphaturia observed in 96% of patients, in two patients (4%) they determined except phosphates also oxalate salt in urine sediment. Patients with phosphate urolithiasis at occurrence of phosphate crystalluria have metabolic state changes: increased serum uric acid concentration from 0.322 ± 0.009 to 0.367 ± 0.018 mmol/l daily renal excretion of inorganic phosphate 23.94 ± 2.93 mmol/day to 32.12 ± 4.39 mmol/day, and reduced total calcium content in urine 6.61 ± 0.94 mmol/day to 3.37 ± 0.89 mmol/day. The results led to the following conclusion.Conclusion. Biochemical signs of occurrence of phosphate crystalluria in patients with stones of infectious origin can be: the approaching level of excretion in the urine of inorganic phosphates to 32,12 ± 4,39 mmol/day, serum uric acid concentration to 0,367 ± 0,018 mmol/l, and the total content of calcium in the urine to 3.37 ± 0.89 mmol/day